2020
DOI: 10.3390/jcm9113633
|View full text |Cite
|
Sign up to set email alerts
|

Professional Assessment of the Impact of COVID-19 on Handling NET Patients

Abstract: The treatment and monitoring of patients with neuroendocrine tumors (NET) has been a major challenge during the COVID-19 pandemic. In a survey, we investigated the influence of COVID-19 on the care of NET patients in the German speaking countries Germany, Austria and Switzerland. The multidisciplinarity of all treating physicians in the outpatient and inpatient sector was reflected in our survey. Furthermore, we were able to present findings pertaining to the university and non-university medical care. Overall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 21 publications
(22 reference statements)
1
19
0
Order By: Relevance
“…However, currently there is no available data regarding the risk of infection, disease status and complications of NEN patients during the COVID-19 pandemic, although several consensus papers have been published reporting some general recommendations 17 , 18 , 19 , 20 , 21 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, currently there is no available data regarding the risk of infection, disease status and complications of NEN patients during the COVID-19 pandemic, although several consensus papers have been published reporting some general recommendations 17 , 18 , 19 , 20 , 21 .…”
Section: Introductionmentioning
confidence: 99%
“…We searched PubMed on April 05, 2021, using the search terms (“novel coronavirus” OR “SARS-CoV2” OR “COVID-19”) AND (“neuroendocrine tumors” OR “neuroendocrine tumours” OR “neuroendocrine neoplasms” OR “neuroendocrine carcinomas” OR “carcinoids”) for articles in English that documented the COVID-19 in patients with NENs. Sixteen articles appeared, including three case reports, 12 recommendations or consensus statements and one only mini-series of four cases among a large thoracic cancers series 19 , 22 , 23 , 24 17 , 18 , 20 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 .…”
Section: Introductionmentioning
confidence: 99%
“…An initial report from the Italian Association for Neuroendocrine Tumors ( ) reported a significant impact of the COVID-19 pandemic on the number of newly diagnosed patients, as well as a reduction in surgical procedures for NET patients and delays in beginning scheduled PRRT [ 13 ]. A lower impact was reported in the study by Krug et al [ 14 ] (published in this Special Issue), who observed that only a minority of physicians reported a major impact of the pandemic on care for NET patients in Germany, Austria, and Switzerland, suggesting different impacts of the COVID-19 pandemic among different areas and health systems, clearly depending on the incidence and dissemination of infections, which, unfortunately, are still increasing.…”
mentioning
confidence: 55%
“…One international survey [85] focusing on colorectal cancer care, with professionals from 84 countries, reported delays in radiologic exams and endoscopic procedures. Other surveys mentioned limited access to hospital facilities (Italy) [89], delays in tissue diagnosis (UK) [88], delays in diagnostics of patients with neuroendocrine tumors (Germany, Austria, Switzerland) [87], and genetic testing or counseling (US) [86]. The other two articles [43, 90] addressed the delays in access to diagnostics, comprising a total of 9 quantitative indicators, from which 8 (89%) signalled an increase in the waiting time to diagnostic procedures.…”
Section: Resultsmentioning
confidence: 99%